Odpowiedź :
G)
3*x+2=-19
3x+2=-19
3x=-19-2
3x=-21/:3
X=-7
H)
6*c-10=14
6c=14+10
6c=24/:6
C=4
I)
8*x+3=43
8x=43-3
8x=40/:8
X=5
J)
5*s-9=-6
5s=-6+9
S=3/5
K)
7-2*x=15
-2x=15-7
-2x=8/:-2
X=-4
3*x+2=-19
3x+2=-19
3x=-19-2
3x=-21/:3
X=-7
H)
6*c-10=14
6c=14+10
6c=24/:6
C=4
I)
8*x+3=43
8x=43-3
8x=40/:8
X=5
J)
5*s-9=-6
5s=-6+9
S=3/5
K)
7-2*x=15
-2x=15-7
-2x=8/:-2
X=-4
Odpowiedź:
g) 3*x+2=-19
3x=-21 /:3
x=-7
3*(-7)+2=-19
h)6*c-10=14
6c=24 /:6
c=4
6*4-10=14
i)8*x+3=43
8x=40 /:8
x=5
8*5+3=43
j)5*s-9=-6
5s=3 /:5
s=⅗
5*⅗ -9=-6
k)7-2*x=15
-2x=8 /: (-2)
x=-4
7-2*(-4)=15
l)6*k+3=33
6k=30 /:6
k=5
6*5+3=33